An Asymmetrical Mixed Higher-Order Discontinuous Galerkin Time Domain Method for Electromagnetic Scattering from the Plasma Sheath around a Hypersonic Vehicle - Jirong Guo; Yiping Han (International Journal of Antennas and Propagation)
The plasma sheath during reentry of hypersonic vehicle is an unmagnetized and weakly ionized nonuniform plasma flow, which causes radio frequency blackout and strong plasma attenuation of electromagnetic wave. The physical properties of the nonuniform plasma flow were obtained using computational fluid dynamics software with unstructured grids. In this study, a detailed computational model was reconstructed with the high-order Lagrange grids for the nonuniform plasma flow region and the high-order Serendipity grids for the homogeneous medium region. In order to calculate the numerical flux between the two types of grids in the discontinuous Galerkin time domain (DGTD) algorithm, an asymmetric high-order element is constructed as a transition unit. Finally, the simulation results in the plasma sphere show that the above method improves the computational accuracy and decreases calculation. The amplitude and scattering about electromagnetic wave in nonuniform plasma flow are clarified in detail. It is suggested that the presented method could be an effective tool for investigating interaction between electromagnetic waves and plasma flow.